An Application of an Adaptive Signal Processing Scheme for a QPSK Signal Demodulation - P. Inban; R. Punchalard; W. Loedwassana; C. Benjangkaprasert (2022 International Electrical Engineering Congress (iEECON), 2022)
An adaptive digital signal processing scheme applied for a digital communication has been presented in the press. The model of an ANC is utilized to demodulate in a coherent detection scheme for a received QPSK signal. The coefficients of the system will be updated by the least mean square (LMS) algorithm that is controlled in the adaptation sequence according to the symbol duration of the received signal. Since such a manner is performed, the system is similar to integrate and dump (I&D) correlator in behavior. The analysis and simulation results have implied that the desired information signal can be recovered from the received signal by the proposed scheme with the same performance as the conventional optimum demodulation.
Keywords: Blind Source Separation Techniques; Advanced Adaptive Filtering Techniques; Advanced Wireless Communication Techniques